Study of diagnostic accuracy of fine needle aspiration cytology of lymph nodes over 6 years in a tertiary care hospital - Barui, Sanghita; Ganguli, Prosenjit; Sanyal, Parikshit; Pathak, Niloy (International Journal of Research in Medical Sciences, 2017)
Background: Lymph node fine needle aspiration cytology (FNAC) is the first line investigation for evaluation of lymph node disease. Existing literature reports high degree of correlation between lymph node FNAC and histological examination. The aim of the present study is to re-evaluate the diagnostic accuracy of FNAC in view of frequent discordance between FNAC and diagnosis on biopsy. Methods: Among a total of 495 lymph node FNACs and 291 biopsies, 69 adequate FNACs which were followed up with biopsy were evaluated with standard statistical methods for assessment of diagnostic accuracy. Results: The commonest diagnosis on biopsy was reactive lymph node (34.71%) followed by granulomatous disease (26.12%) and lymphoid neoplasms (20.96%). Reactive lymphadenitis and granulomatous disease were also the two commonest categories on FNAC (34.34% and 24.85% respectively). However, the sensitivity of FNAC in diagnosis of granulomatous disease was found to be 45.83%, which increases to 70.03% if necrosis is included as a marker of granulomatous disease. The greatest sensitivity was achieved in diagnosis of metastatic disease (88.89%), followed by lymphoid neoplasms (69.23%). Conclusions: FNAC is a useful tool for excluding specific categories of lymph node diseases, esp. metastatic disease. However, the technique needs improvement as to sample more representative areas of the node, to improve its sensitivity.